O impacto da governança da internet sob o prisma da soberania - Gatto, Raquel Fortes (2008)
The Information Society has been changed by the Technological Revolution and its main element: Internet, which leads to the revision of the traditional social and legal standards, such as the sovereignty and international players, facing the virtual reality challenges. The Internet is an international public good or an space with no borders that reaches all mankind. The Internet Governance claims that all countries set a consensus about the cyberspace having multiple sovereignties but none in particular, such as the Sea Convention (Montego-Bay Agreement). The Internet Governance mechanisms includes technical (Internet standards and protocols), social (social boundaries, virtual communities, digital divide), economical (electronic commerce, technology access), legal, and others. The Internet Governance players are: governments, private sector, civil society and international organizations. This research has the objective to discuss the sovereignty concept all the way through the history of Internet Governance mechanisms. The methodology concerns the bibliographical review. The scientific literature available is short, due to the fact that Internet is a recent phenomenon. Data resources are documents from the international events (World Summit on Information Society and Internet Governance Forum); Internet governance organizations (Internet Engineering Task Force and ICANN); and interviews with Internet specialists. In conclusion, there is no break face the actual sovereignty concept, although there is some new characteristics such as the multistakeholder participation throughout the soft law